Effect of cold atmospheric microwave plasma (CAMP) on wound healing in canine keratinocytes - Lertpatipanpong, Pattawika; Sillapachaiyaporn, Chanin; Oh, Garam; Kang, Yeong-Hun; Hwang, Cheol-Yong; Baek, Seung Joon (Frontiers in Cell and Developmental Biology, 2023)
Cutaneous wound healing is a biological process that occurs upon skin injury and involves different mechanisms to repair tissue damage. Improper healing or prolonged curation period of wound lesions may induce unpleasant complications. Cold Atmospheric Microwave Plasma (CAMP) is an upcoming medical therapeutic option for skin infection and wound treatment. However, the molecular mechanisms of CAMP-mediated canine wound healing are not well characterized. Wound healing activity was examined to elucidate the biological effects and molecular mechanisms of CAMP. Canine keratinocytes (CPEK) were treated using CAMP, and their wound-healing activities were evaluated. The molecular mechanisms of that effect were examined, based on RNA-seq analysis data, verified using immunoblotting and polymerase chain reaction. It was found that the CAMP-treated cells exhibited a significant increase in cell migration evaluated by scratch assay in human keratinocytes (HaCaT) and canine keratinocytes (CPEK). Additionally, CAMP-treated CPEK cells showed a significant positive effect on cell invasion. The RNA-seq data revealed that CAMP alters different genes and pathways in CPEK cells. The gene expression involved in the cell cycle, cell proliferation, angiogenesis, cell adhesion, and wound healing was upregulated in CAMP-treated cells compared with gas control. The hippo pathway was also analyzed, and the protein and mRNA levels of YAP were significantly increased in CAMP-treated cells. CAMP-treated CPEK cells indicated the downregulation of E-cadherin and upregulation of Vimentin, Snail, and Slug at transcription and translation levels, contributing to a favorable effect on cell migration. Our findings suggested that CAMP treatment provided beneficial effects for the curative wound process through induction of genes involved in wound healing, promotion of EMT, and increase of the molecular targets in the hippo signaling pathway.